'Waiting and Wanting': older peoples' initial experiences of adapting to life in a care home: a grounded theory study. Issue 2 (16th February 2022) - O'Neill, Marie; Ryan, Assumpta; Tracey, Anne; Laird, Liz
Abstract: A grounded theory approach, consistent with the work of Strauss and Corbin, was used to undertake semi-structured interviews with 17 older people, to explore their experiences of living in a care home, during the four- to six-week period following the move. Purposive sampling was initially adopted, thereafter, theoretical sampling was employed to recruit individuals identified by care managers within older peoples' community teams and care home managers within a large Health and Social Care Trust in the United Kingdom. Consistent with grounded theory methodology, data collection and analysis occurred simultaneously. Constant comparative analysis underpinned data analysis and data management techniques. Data analysis revealed five distinct categories that captured these experiences. These were: (a) wanting to connect – 'I am so lost here', (b) wanting to adapt – 'Well mentally you have to make the best of it', (c) waiting for assistance – 'it's a frustration for me', (d) 'waiting on the end' – I am making no plans' and (e) wanting to re-establish links with family and home – 'I love getting home and I like getting out to the town'. Together these five categories formed the basis of the core category, 'Waiting and Wanting', which encapsulates the initial adaptation experiences of the men and women in the study. Findings indicate that individuals were dependent on others to create a sense of belonging, independence and wellbeing. Moreover, risk aversive practices were perceived as a threat to individuals' independence and autonomy. Recommendations include the need to amend policy and practice for the development of a bespoke induction programme for each resident facilitated by a senior member of the care home staff working in partnership with individuals and families, in addition to the health and social care team, to support a more positive transition for new residents, relatives and care home staff.